Semi-probabilistic design of rainwater tanks: a case study in Northern Italy. Issue 3 (16th March 2018) - Becciu, G.; Raimondi, A.; Dresti, C.
Abstract: The paper proposes a semi-probabilistic approach for the design of rainwater tanks. In particular, the cumulative distribution function of the active storage is derived as a function of rainfall moments. The model is validated through continuous simulation of the hydraulic behaviour of a hypothetical rainwater tank located in Milan (North Italy) using as input a series of rainfall records.